The Analysis of Insulting Practices - Sticks and Stones in the Croatian Parliament - Vančura, Alma; Tomić, Diana (2013)
The aim of this paper is to study the forms and functions of insults in the Croatian Parliament and compare them with recorded instances of insults found in the British and the Swedish parliaments. The corpus for analysis includes transcripts of two sessions of the 6th Parliamentary assembly and 5 randomly selected sessions from each of the previous assemblies. The corpus includes Aktualno prijepodne (i.e. Question time) as well. Levels of analysis are: forms of (un)parliamentary polarization, mitigation strategies and identification of convergence (between a group of like-minded politicians) and divergence (between opposing groups) by usage of insults and derogatory terms. Reactions to the insults were analyzed as part of the identification process, as it was noted that the Members of Parliament (MPs) were often offended by the insult and wanted to comment on it, even when the insult was not personally addressed to them. The results show, as expected, that the MPs of the Croatian Parliament are polarized. The offensive expressions are based on pathos in first Assemblies, while later change to ethos-oriented logos, mainly trying to discredit the MPs credibility, with occurrences of ad hominem arguments. The preferred mitigation strategies are attribution transfer, followed by formulation of insults as questions rather than statements. Unification of politicians is purely along the party-line and is shown through forms of address, the procedures to respond to offensive phrases, labeling and stereotypes.
ENG